2011
DOI: 10.1007/s00464-011-1737-7
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency ultrasound probe sonography staging for colorectal neoplasia with superficial morphology: its utility and impact on patient management

Abstract: The impact of HFUPS on the treatment of SCN depends on their endoscopic characteristics. It is negligible for low-risk SCNs, and these lesions can be treated on the basis of their endoscopic appearance alone. Nevertheless, compared with endoscopy alone, HFUPS changed the subsequent therapeutic approach in a positive way for up to 42% of high-risk lesions, including those with a depressed component and an invasive pit pattern. These endoscopic features can therefore be recommended as the entry criteria for an H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Endoluminal endoscopic ultrasound shows more promise. For T staging, before removal of a suspicious polyp, endoscopic ultrasound has a reported accuracy of 66-93% [160,[213][214][215][216]. Hurlstone et al [213] showed a high level of accuracy in staging malignant polyps.…”
Section: Assessing Depth Of Invasionmentioning
confidence: 99%
“…Endoluminal endoscopic ultrasound shows more promise. For T staging, before removal of a suspicious polyp, endoscopic ultrasound has a reported accuracy of 66-93% [160,[213][214][215][216]. Hurlstone et al [213] showed a high level of accuracy in staging malignant polyps.…”
Section: Assessing Depth Of Invasionmentioning
confidence: 99%
“…EUS has been considered useful for tumor staging of colorectal cancers; however, its real clinical impact for deciding on the indication for surgical operation is still not clear [13][14][15]. In the present EUS study, when the change for the third layer (submucosal layer) was 1 millimeter or more the histological SM invasion depth was 4.3 mm.…”
Section: Discussionmentioning
confidence: 55%
“…Imaging methods used to diagnose tumour size and the degree of malignant invasion have limited sensitivity and specificity . Determining the relationship between the size of residual rectal wall lesions after neoadjuvant CRT and the pathological response was the subject of a study by Smith et al .…”
Section: Discussionmentioning
confidence: 99%
“…When selecting patients suitable for total mesorectal excision, careful preoperative staging is especially important, as well as a perfect surgical technique with excision of the lesion across the full thickness of the rectal wall with a 10-mm border of macroscopically healthy tissue [18,19]. Imaging methods used to diagnose tumour size and the degree of malignant invasion have limited sensitivity and specificity [20][21][22][23][24]. Determining the relationship between the size of residual rectal wall lesions after neoadjuvant CRT and the pathological response was the subject of a study by Smith et al [7].…”
Section: Discussionmentioning
confidence: 99%